A environmental education in science museums in the city of Belo Horizonte, Minas Gerais - Padoan, Lucas de Lima Fernandes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
When addressing the issue of environmental education, it is generally agreed the concern with the environment as well as a unanimous recognition of the crucial role of education in individual and collective awareness process. Thus, this work has as main objective to discuss the relations and the applicability of environmental educationin non-formal spaces of education, offering a major focus in two museum institutions in Belo Horizonte, Minas Gerais:: Espaço do Conhecimento UFMG e Museu de História Natural e Jardim Botânico da UFMG. So, we will discuss environmental education projectsand science education that are applied in such museums, making it possible to evaluate and reflect on the social role of such spaces. Finally, we point out that environmental education it ceases to be just a "form" of education among many; is not only a tool for solving problems or environmental management, it is therefore an essential dimension of basic education with regard to a group of interactions that underlies the personal and social development.